Maternità Surrogata e Adozione in Casi Particolari - Molinaro, Francesco Reis (Revista Amagis Jurídica, 2025)
The paper, after highlighting the persistent reasons for the ban on surrogacy, focused on the solution identified by Italian jurisprudence (adoption in special cases) to reconcile the ban on gestation on behalf of others and the need to ensure full protection for the child born. This institution, despite the adjustments made by jurisprudence, still does not seem to guarantee full protection for the born child. Therefore, in the author’s opinion, it would be necessary for the legislature to intervene and, by enhancing the peculiarities of surrogacy, introduce a new adoptive figure that is not based on the requirement of the state of abandonment but revolves around the existence of a parenting project and a concrete and genuine emotional bond between the couple and the born child.